Maladaptive Perfectionism and the Impact of Fibromyalgia: A Serial Mediation Model Through Sleep Reactivity, Insomnia Severity, and Pain Catastrophizing - Sirleaf, Siaka; Carroll, Danny (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to examine the association between maladaptive perfectionism and fibromyalgia impact and to test the serial mediating roles of sleep reactivity, insomnia severity, and pain catastrophizing. This cross-sectional, descriptive-correlational study included 300 adults with physician-diagnosed fibromyalgia residing in Canada. Participants were recruited from rheumatology and chronic pain clinics, community organizations, support groups, and online patient networks. Data were collected using the Discrepancy subscale of the Almost Perfect Scale–Revised, the Ford Insomnia Response to Stress Test, the Insomnia Severity Index, the Pain Catastrophizing Scale, and the Revised Fibromyalgia Impact Questionnaire. Pearson correlations and serial mediation analysis were conducted using IBM SPSS Statistics 29 and PROCESS Model 6. Age, gender, fibromyalgia duration, average pain intensity, and sleep-medication use were controlled. Indirect effects were tested with 10,000 bias-corrected bootstrap resamples. Maladaptive perfectionism significantly predicted sleep reactivity, insomnia severity, pain catastrophizing, and fibromyalgia impact. Sleep reactivity significantly predicted insomnia severity and pain catastrophizing, whereas insomnia severity significantly predicted pain catastrophizing and fibromyalgia impact. Pain catastrophizing was the strongest unique predictor of fibromyalgia impact. The complete serial indirect pathway from maladaptive perfectionism through sleep reactivity, insomnia severity, and pain catastrophizing to fibromyalgia impact was significant. All specific indirect effects were also significant, and the total indirect effect accounted for a substantial proportion of the overall association. The final model explained 69.6% of the variance in fibromyalgia impact. The remaining direct effect of maladaptive perfectionism was significant, indicating partial mediation. Maladaptive perfectionism may increase fibromyalgia burden through heightened stress-related sleep vulnerability, more severe insomnia, and stronger catastrophic interpretations of pain, supporting integrated interventions targeting perfectionistic self-evaluation, sleep disturbance, and pain-related cognition.